Axisymmetric saturated granular column collapses at elevated gravitational accelerations - Webb, William (2024)
Debris flows represent a prevalent natural hazard, posing a significant threat to communities and infrastructure located in mountainous regions susceptible to intense precipitation events worldwide. Furthermore, the escalating impacts of climate change are poised to intensify both the frequency and severity of these events. The dynamics of debris flows, in contrast to other geophysical granular flows, exhibit heightened complexity owing to substantial fluid volumes and a broad spectrum of particle sizes present within the flow. The diverse composition of debris flows gives rise to highly heterogeneous flow states, wherein many contributing mechanisms, notably the interplay between the granular and fluid phases, remain inadequately understood within the wider scientific community. Consequently, there persists a lack of consensus on the optimal approach to incorporate the influence of grain-fluid interactions into numerical models which are essential for predicting debris flow behaviour and formulating effective mitigation strategies.